2014
DOI: 10.9790/5933-0332542
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Derivatives Market in India and its Current Position in Global Financial Derivatives Markets

Abstract: Rs.2365 Cr. in 2000-2001 to Rs. 26444804.86 Cr. in 2013

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Agarwal et al [9] examined the effect of derivatives on diverse stock features such as valuation, price effectiveness and liquidity and found that derivatives put in value by improving price competence and liquidity of the stock. Shalini and Raveendra [10] suggested that globalization and liberalization across the world have increased the financial risk. It was found that equity derivatives play an important in price-discovery, hedging strategies; innovations in financial engineering are driving financial derivatives.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Agarwal et al [9] examined the effect of derivatives on diverse stock features such as valuation, price effectiveness and liquidity and found that derivatives put in value by improving price competence and liquidity of the stock. Shalini and Raveendra [10] suggested that globalization and liberalization across the world have increased the financial risk. It was found that equity derivatives play an important in price-discovery, hedging strategies; innovations in financial engineering are driving financial derivatives.…”
Section: Theoretical Backgroundmentioning
confidence: 99%